JLPG 2019
DOI: 10.7176/jlpg/86-09
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Contraceptives in Nigeria: Benefits, Challenges and Probable Solutions

Abstract: This work examines the decision-making processes among couples, and explained the benefit, challenges and probable solutions to the use of contraception in Nigeria. This work is predicated on the premise that contraceptive decision-making is a complex process that involves an array of factors and structural forces that operate and intersect at different levels to influence decision-making on one hand and the dearth of legal framework to regulate the proper and correct use of contraceptives in Nigerian Reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…34 Individuals who are sexually active see the need to prevent unwanted pregnancy, STIs, pregnancy-related health risks and delay marriage to complete education while in sexual relationships. 9,10,45 It also helps girls and women achieve empowerment to live a healthy and economically productive life. Studies have shown that sexually inactive young often cite their sexual inactivity as a reason for non-use.…”
Section: Discussionmentioning
confidence: 99%
“…34 Individuals who are sexually active see the need to prevent unwanted pregnancy, STIs, pregnancy-related health risks and delay marriage to complete education while in sexual relationships. 9,10,45 It also helps girls and women achieve empowerment to live a healthy and economically productive life. Studies have shown that sexually inactive young often cite their sexual inactivity as a reason for non-use.…”
Section: Discussionmentioning
confidence: 99%
“…1 Fertility control has been practiced since times immemorial, but effective and safe methods of birth control only became available around the 20th century. 2 The use of contraceptives has helped in managing the poverty crisis owing to overpopulation despite its discouragement by certain cultural sects, religious, political, and moral beliefs. 3,4 In 2019, there were 1.9 billion women within the reproductive age range of 15 to 49 years in the World, and 1.1 billion of these women need some kind of contraception.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 The utilization of contraceptives in Nigeria has remained persistently inadequate, despite the numerous advantages and various initiatives by governmental and developmental entities to enhance their adoption, this progress has been retarded due to high illiteracy, poverty, and less awareness among people in the rural areas. 2 In addition, data from the Nigeria Demographic and Health Survey stated that there was a remarkable surge in the utilization of contemporary contraceptive methods, which rose from 4% to 12% over a span of 28 years namely; 1990 -2018. 2,9 Herbal contraceptive techniques have been utilized for centuries across various cultures and traditions, and they present numerous advantages over synthetic hormones, intrauterine devices, or surgical interventions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation